Nondestructive Real‐Time Monitoring of Enhanced Stem Cell Differentiation Using a Graphene‐Au Hybrid Nanoelectrode Array. Issue 39 (2nd August 2018) - Lee, Jin‐Ho; Choi, Hye Kyu; Yang, Letao; Chueng, Sy‐Tsong Dean; Choi, Jeong‐Woo; Lee, Ki‐Bum
Abstract: Stem cells have attracted increasing research interest in the field of regenerative medicine because of their unique ability to differentiate into multiple cell lineages. However, controlling stem cell differentiation efficiently and improving the current destructive characterization methods for monitoring stem cell differentiation are the critical issues. To this end, multifunctional graphene–gold (Au) hybrid nanoelectrode arrays (NEAs) to: (i) investigate the effects of combinatorial physicochemical cues on stem cell differentiation, (ii) enhance stem cell differentiation efficiency through biophysical cues, and (iii) characterize stem cell differentiation in a nondestructive real‐time manner are developed. Through the synergistic effects of physiochemical properties of graphene and biophysical cues from nanoarrays, the graphene‐Au hybrid NEAs facilitate highly enhanced cell adhesion and spreading behaviors. In addition, by varying the dimensions of the graphene‐Au hybrid NEAs, improved stem cell differentiation efficiency, resulting from the increased focal adhesion signal, is shown. Furthermore, graphene‐Au hybrid NEAs are utilized to monitor osteogenic differentiation of stem cells electrochemically in a nondestructive real‐time manner. Collectively, it is believed the unique multifunctional graphene‐Au hybrid NEAs can significantly advance stem‐cell‐based biomedical applications. Abstract : Multifunctional graphene–Au hybrid nanoelectrode arrays (NEAs) are developed. Owing to the combinatory effect of graphene and biophysical cues, the graphene–Au hybrid NEA shows highly improved cell adhesion and spreading behavior, which results in enhanced osteogenesis. Additionally, improved electrochemical sensitivity allows the monitoring of osteogenic differentiation in a nondestructive real‐time manner.